Tipologi Korupsi Serta Penanganan yang Berkepastian Hukum dan Keadilan - Yusrizal Yusrizal (Jurnal Ilmu Hukum Reusam, 2015)
The concept of state law (rechtstaat) relating to corruption cases has to be conducted by implementing law enforcement, law certainty, and justice. Any kind of policy in relation to corruption eradication has to be done based on the application of legislation. The rule of legal officers in eradicating corruption is highly influenced by the integrity of morality and personal ethics (the maturnity of spiritual intelligence) by having good understanding on corruption eradication which is very significant in making a decision in relation to corruptor.